(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2025)
The article provided contextual evidence and operational recommendations for local decision-making and the planning of small-scale bioenergy policies. Its objective is to assess the use of forest species for energy purposes (firewood and charcoal) in rural parishes of Esmeraldas, Ecuador, and to propose guidelines for their sustainable management within the framework of rural development. A descriptive approach with an exploratory scope was applied, combining bibliographic and documentary review with fieldwork (direct observation). The information was organized considering criteria of availability, reported energy yield, regeneration times, and harvesting pressure. According to the sources consulted, in the study area, the demand for firewood and charcoal was concentrated on a few species: laurel (Cordia alliodora), guayacán (Tabebuia chrysantha), and guadua (Guadua angustifolia), which intensified the pressure on secondary forests and remnants; likewise, management gaps were identified that endanger the sustainability of the resource and local energy security. Based on the analysis, it was concluded that management should focus on prioritizing fast-growing species, promoting community forestry with defined rotations, formalizing harvesting practices through local agreements and participatory control, diversifying energy sources, and improving the efficiency of their use.